AStudy of the effect of propolis extract (Bee glue) in reducing toxicity of Acrylamide in female rats. - AL-Maeeali, Hussein K.A. (University of Thi-Qar Journal of Science, 2019)
The present study was designed to determine the toxic effects of Acrylamide on Liver and Kidney organs functions and parameters blood in female rat, as well as, the evaluation of the benefit role of Propolis in relieving these effects in female rat. The results revealed that in studied, which were as follows: Significant decrease (P<0.05) in body weight, body weight gain compared control group.Significant increase (P<0.05) in Liver weight and Significant decrease (P<0.05) in kidneys weight compared control group. Significant decrease (P<0.05) in RBCs count, Hb estimation and PCV, WBCs compared control group. Significant decrease (P<0.05) in total protein and albumin compared control group, and significant increase (P<0.05) in total globulin, Creatin and Urea compared control group.Significant increase (P<0.05) in ALT, AST enzymes compared control group. The histopathological results revealed a blood vessel congestion and tissue hemorrhage, in each of liver, kidneys, as well as, while the tubular epithelial cells suffered from necrosis. The hepatocytes showed a necrotic and degenerative, and an increase in the number of kupffer cells. On the other hand, the results revealed that supplementation of porpolis with provender will relieve the toxicological effects of acrylamide, in all parameters included in this study. It can be concluded that the exposure to porpolis present led to an toxicological changes, while Acrylamide supplementation relieve these effects, as well as its role in retention of Acrylamide